Kinin B1 Receptor Antagonist BI113823 Reduces Acute Lung Injury*. Issue 11 (November 2015) - Nasseri, Saeed; Gurusamy, Malarvizhi; Jung, Birgit; Lee, Dongwon; Khang, Gilson; Doods, Henri; Wu, Dongmei
Abstract : Objectives: This study was undertaken to examine the effects of BI113823, a potent small molecule orally active nonpeptide B1 receptor antagonist, in an experimental model of endotoxin-induced direct lung injury in mice and indirect lung injury and survival in cecal ligation and puncture–induced polymicrobial sepsis in rats. Design: Experimental, prospective study. Setting: University research laboratory. Subjects: Male BALB/c mice and male Wistar rats. Interventions: Series 1: acute lung injury was induced in mice by intratracheal injection of lipopolysaccharide. Mice were then randomly assigned to receive treatment of vehicle, BI113823, or dexamethasone. Bronchoalveolar lavage fluid and lung tissues were analyzed for inflammatory cell influx and various histologic variables. Series 2: sepsis was induced by cecal ligation and puncture in anesthetized rats. Animals were then randomly assigned to receive treatment of vehicle or BI113823. Experiments were terminated at 20 hours and 7 days following cecal ligation and puncture, respectively. Measurements and Main Results: Series 1: treatment with BI113823 significantly reduced lipopolysaccharide-induced neutrophil influx in bronchoalveolar lavage fluid. The BI113823 group had significantly lower lung vascular permeability, lung water content, myeloperoxidase activity, lung apoptosis and lung injury scores, total protein content, and tumor necrosis factor-α and interleukin-1β levels compared with vehicle controls. In addition, nuclear factor-κB phosphorylation, nuclear translocation, and cyclooxygenase-2 and inducible nitric oxide synthase expression in the lung were attenuated in BI113823-treated animals compared with vehicle controls. Series 2: BI113823 significantly reduced sepsis-induced macrophage recruitment, protein content, and tumor necrosis factor-α and interleukin-1β levels in lavage fluid and also reduced lung water content and plasma levels of tumor necrosis factor-α and interleukin-6 compared with vehicle controls. Most importantly, treatment with BI113823 significantly improved survival following severe sepsis in rats. Conclusions: Administration of B1 receptor antagonist BI113823 significantly reduced endotoxin-induced direct lung injury and also reduced sepsis-induced lung inflammatory response. Most importantly, BI113823 improved survival following severe polymicrobial sepsis.